التغيرات المناخية و أثرها على الإنتاج الزراعي في ولاية شمال دارفور - السودان - يعقوب، إسحق إبراهيم هدي (جامعة البصرة - كلية الآداب, 2013)
تناولت هذه الورقة إثر التغيرات المناخية على الإنتاج الزراعي بولاية شمال دارفور التي تقع في اقصي غرب جمهورية السودان بين دائرتي عرض (13° - 20° شمالا)، وخطي طول (24 ° - 40 27 ° شرقا)، وذلك لعرض بعض النماذج العلمية التي تؤكد حدوث التغيرات المناخية في منطقة الدارسة، مع تحديد مخاطرها على الانتاج الزراعي، والمساهمة في صياغة رؤية واضحة على المستوي الوطني لدمج قضية تغير المناخ في السياسات الزراعية. واستندت الدراسة على عنصري الحرارة والامطار في تحديد التغيرات المناخية في منطقة الدراسة بوصفهما أكثر العناصر المناخية تأثيرا على الانتاج الزراعي. وتم جمع بيانات الانتاج للمحاصيل الزراعية الرئيسة في منطقة الدراسة (الدخن والذرة)، وشملت البيانات المساحات المزروعة، وكميات الانتاج، ومقارنتها مع كميات الامطار والحرارة التي سادت في منطقة الدراسة. ودلت نتائج هذه الدراسة الي ان هنالك تغيرات جذرية حدثت للمناخ في منطقة الدراسة، واثرت بدورها في الانتاج الزراعي من حيث المساحات والكميات المنتجة للمحاصيل الزراعية، حيث مثلت الامطار اهم العناصر المناخية التي تأثرت بها العملية الزراعية في منطقة الدراسة. واوصت الدراسة بضرورة الاهتمام بظاهرة التغير المناخي في ولاية شمال دارفور وتأثيراتها على الانتاج الزراعي، هذا مع اجراء المزيد من البحوث العلمية في هذا الخصوص. Dealt with this paper impact of climate change on agricultural production in North Darfur state, which is located in the far west of the Republic of Sudan between latitudes (13° - 20° north), and longitudes (24 ° - 40 '27 ° east longitude), so as to offer some scientific models that stresses of climate change in the study area, identifying risks to agricultural production, and to contribute to the formulation of a clear vision on the national level to integrate the issue of climate change in agricultural policy. The study was based on a racist temperature and precipitation in determining the climate changes in the study area as the most influential elements of climate on agricultural production. Production data was collected for the main agricultural crops in the study area (millet and sorghum), and data included acreage, production quantities, and compare it with rainfall and temperatures that prevailed in the study area. The results of this study showed that there are radical changes have taken place in the climate of the study area, and in turn influenced in terms of agricultural production areas and quantities of agricultural crops; where rainy represented the most important climatic elements that have been affected by the agricultural process in the study area. The study recommended the need for attention to the phenomenon of climate change in the state of North Darfur and its impact on agricultural production, with this further scientific research in this regard
Keywords: تغيرات المناخ -- الإنتاج الزراعي -- دارفور -- السودان